2006
DOI: 10.1300/j005v31n01_11
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 11

Abstract: This study explored the sense of community among women (n = 21) and women with children (n = 30) living in Oxford Houses, with emphasis on how the presence of children might affect the household. Sense of community did not vary between participants with more or less than three months residence. Residents reported very high levels of satisfaction with the home, possibly because of a ceiling effect of little room for increases in their sense of community over time. Participants reported that they were getting al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Studies by Olson, Curtis, Jason, Ferrari, Horin, and Davis (2003) and d’Arlach, Olson, Jason, and Ferrari (2006) found average PSCS scores were higher among women who lived in Oxford Houses. A study by Alvarez, Adebanjo, Davidson, Jason, and Davis (2006) found that a matched sample of deaf and hearing participants scored similarly on PSCS scores.…”
Section: Sense Of Community Among Adults In Substance Abuse Recoverymentioning
confidence: 95%
“…Studies by Olson, Curtis, Jason, Ferrari, Horin, and Davis (2003) and d’Arlach, Olson, Jason, and Ferrari (2006) found average PSCS scores were higher among women who lived in Oxford Houses. A study by Alvarez, Adebanjo, Davidson, Jason, and Davis (2006) found that a matched sample of deaf and hearing participants scored similarly on PSCS scores.…”
Section: Sense Of Community Among Adults In Substance Abuse Recoverymentioning
confidence: 95%
“…The finding that social support contributes to recovery brought about novel continuum of care options, including therapeutic communities, halfway houses, and sober living housing (Polcin et al, 2010; Yablonsky, 1989). However, d'Arlach, Olson, Jason, and Ferrari (2006) found that few recovery houses in the United States are specifically designed for women with substance use problems. Although there is growing research on gender specific treatment for substance use problems, there is little research on housing for women.…”
Section: Introductionmentioning
confidence: 99%
“…For example, d'Arlach and colleagues (2006) studied the effects of the presence of women with children on the other women in the house who did not have children. Residents in this study reported that having children in the household had positive effects on their recovery by enabling them to feel useful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings indicated that children in the house supported the recovery of house members and on improving parent–child relationships. In general, studies on these OHs have shown high levels of parent reports of child satisfaction (d’Arlach, Olson, Jason, & Ferrari, 2006), but children living in these settings had not been directly interviewed. Similarly, houses with parents and children have been shown to foster assertiveness and self-confidence in the women residents, which are important aspects of the recovery process specifically faced by females (Davis et al, 2006; Timpo et al, 2014).…”
mentioning
confidence: 99%